Role of Homestay Tourism in Preserving Tharu Culture and Boosting Rural Economy of Nepal: Evidence from Bhada Village of Kailali District (Panauti Journal, 2025)
Home stay tourism has emerged as a significant source of family income in Nepal’s rural destinations. This study assesses the role of home stay tourism in preserving Tharu culture and boosting the rural economy in Bhada Village of Kailali District—the first community home stays initiative in Sudur Paschim Province, established in 2010. The study used a descriptive and explanatory research design under a quantitative approach and a cross-section survey strategy. Required data were collected from randomly selected 45 households (20 home stay owners and 25 local farmers and cultural performers) through self-administered household survey questionnaires. The study found the popularity of the destination due to its religious and cultural assets, particularly the Vehada Baba Temple and indigenous Tharu culture. The village is rich in forest ecosystem and traditional Tharu lifestyle. These attractions draw tourists annually, fostering cultural exchange and economic growth. The study reveals that home stays have significantly improved local livelihoods by generating employment and increasing household incomes, with many owners earning between NRs. 25,000 to 50,000 per month. Additionally, tourism has encouraged the preservation of Tharu culture, arts, and traditions, promoting them at national and international levels. In conclusion, home stay tourism in Bhada Village serves as a model for community tourism, demonstrating how rural areas can improve livelihoods through home stay tourism. Therefore, provincial and local authorities should establish clear operational guidelines and designate responsible agencies for home stay registration, monitoring, and quality assurance to strengthen community home stays in the province.